2019
DOI: 10.3389/fimmu.2019.01622
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptome Analysis of Immune Response of mIgM+ B Lymphocytes in Japanese Flounder (Paralichthys olivaceus) to Lactococcus lactis in vitro Revealed That IFN I-3 Could Enhance Their Phagocytosis

Abstract: B cells have recently been proven to have phagocytic activities, but few studies have explored the relevant regulation mechanisms. In this study, we showed that the Japanese flounder ( Paralichthys olivaceus ) membrane-bound (m)IgM + B lymphocyte population could phagocytose inactivated Lactococcus lactis with a mean phagocytic rate of 25%. High-purity mIgM + B lymphocytes were subsequently sorted to investigate the cel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 46 publications
(59 reference statements)
0
15
0
Order By: Relevance
“…We did not examine the lymph nodes for the innate immune response due to our concern that the fixation of animals and the collection of blood may lead to unexpected abortion, and as a consequence, it may interfere with our evaluations on the safety of the S2 vaccine, since abortion is an important parameter in our evaluation in this study. The use of the peripheral blood for the isolation of lymphocytes for transcriptomic analysis is not new, as the use of the peripheral blood from pigs ( 30 ), dogs ( 31 ), Chinese geese ( 32 ), and humans ( 33 35 ), including patients with COVID-19 ( 36 ), have been well-documented.…”
Section: Discussionmentioning
confidence: 99%
“…We did not examine the lymph nodes for the innate immune response due to our concern that the fixation of animals and the collection of blood may lead to unexpected abortion, and as a consequence, it may interfere with our evaluations on the safety of the S2 vaccine, since abortion is an important parameter in our evaluation in this study. The use of the peripheral blood for the isolation of lymphocytes for transcriptomic analysis is not new, as the use of the peripheral blood from pigs ( 30 ), dogs ( 31 ), Chinese geese ( 32 ), and humans ( 33 35 ), including patients with COVID-19 ( 36 ), have been well-documented.…”
Section: Discussionmentioning
confidence: 99%
“…To date, whether type I or type II IFNs affect B cell functionality has been only addressed in fish in one study in which flounder ( Paralichthys olivaceus ) type I IFN was shown to enhance the phagocytic capacity of IgM + B cells as well as their production of reactive oxygen species (ROS) ( 45 ). In the current study, we have investigated the effects of both type I and type II IFN on IgM + B cells using rainbow trout ( Oncorhynchus mykiss ) as a model species.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, to obtain all CD4 + cells in peripheral blood leukocytes, the leukocytes were incubated with a mixture of CD4-1 and CD4-2 mAbs as the primary antibody. The method of isolation of CD4 + T cells was performed as previously described 55 . Briefly, after the primary antibody, the leukocytes were incubated with goat anti-mouse IgG magnetic beads (Miltenyi Biotech, Germany).…”
Section: Methodsmentioning
confidence: 99%